Xenotransplante de ovário bovino na cápsula renal de camundongas BALB/c Nude e C57BL6 SCID estimuladas com eCG ou associação de FSH e LH - Pimentel, Muriel Magda Lustosa (Universidade Federal Rural do Semi-Árido, 2015)
This study was aimed at evaluating the viability of xenografting of ovarian tissue from heifers under renal capsule of two different murine models of hormone-treated renal-encapsulated bovine ovarian tissue xenotransplantation. Thus, animals of BALB/c Nude (n=9) and C57BL6 SCID (n=12) received ovarian cortical fragments from seven heifers. The ovarian cortices were processed for histology (control) or grafted under the renal capsules of recipient mice, evaluated by vaginal washing until 60th day post-grafting and divided in three groups, each one with three BALB/c Nude and four C57BL6 SCID, as: control group; treated with equine chorionic gonadotrophin hormone, eCG or a combination of follicle stimulating hormone and luteinizing hormone (FSH + LH). Infrared thermography was performed at different times in donor ovaries and recipients: at collection at slaughterhouse, at the time of xenografting procedure and at time of xenografts collection, grafted tissues were also recovered for histology and blood was collected for hepatorenal biochemistry. The average duration of the phases of the estrous cycle, the results of thermographic evaluation, and hepatorenal biochemistry were compared by ANOVA followed by Tukey s test (p<0,05) The average time of xenografting did not exceeded 18 minutes in both models. The C57BL6 SCID showed a more elastic renal capsule, facilitating the grafting procedure whem compared to BALB/c NUDE. Among the strains, 83% of C57BL6 SCID and 77% of BALB/c Nude mice showed development and vascularization of the transplanted tissue, which acquired cyclicity at 19 and 9 days post-transplantation, respectively. Hemorrhagic follicles in xenografts induced with FSH + LH were found in the C57BL6 SCID strain. The thermography did not allows clearly distinction between donor and recipient tissue by xenografting. Our integration of these parameters revealed no significant difference between treatments for both strains studied, with the exception of urea levels, which were lower in the grafted mice than in non-grafted control mice. In conclusion, histological evaluation allow the monitoring of graft reperfusion and follicular development; new hormonal protocols are needed for obtaining oocytes for in vitro fertilization; infrared thermography provided minimum accuracy for monitoring donor ovaries and the kidney recipient, not highlighting transplants; C57BL6 SCID strain appears to be the best host for ovarian xenografts, since the transplants in these mice were viable and showed robust follicular development and xenotransplantation under the kidney capsule does not compromise the renal and hepatic function of the recipient animal
Xenografting of bovine ovaries under renal capsule of BALB-c/Nude and C57BL6 SCID mice stimulated with eCG or association of FSH and LH
Keywords: Heifers; Mice; Ovary; Novilhas; Camundongas; Ovário; CIENCIAS AGRARIAS::MEDICINA VETERINARIA